2020
DOI: 10.4103/ajns.ajns_52_20
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of anterior reconstruction with rib grafts in tuberculosis of the thoracic spine

Abstract: Introduction: Tricortical iliac bone is the gold standard as an autograft for the reconstruction of the anterior column in tuberculosis (TB) of the thoracic spine. However, the quantity of graft needed is significant. It creates a considerable defect in the pelvic bone, causing graft site complications, including pain, pelvic instability, fractured ilium, herniated muscle, or abdominal contents. To prevent these donor site morbidities, ribs that were removed during the versatile approach were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Rib bone grafts are known for their biological potential and ability to achieve rapid bone fusion [ 32 34 ], our study revealed that all patients who received the autogenous multi-fold rib graft achieved bony fusion within an average duration of 7.97 ± 2.34 months. A notable advantage of the rib graft is the absence of a need for an extra incision: the rib bone strut required for grafting is excised during routine anatomical dissection of the surgical procedure.…”
Section: Discussionmentioning
confidence: 83%
“…Rib bone grafts are known for their biological potential and ability to achieve rapid bone fusion [ 32 34 ], our study revealed that all patients who received the autogenous multi-fold rib graft achieved bony fusion within an average duration of 7.97 ± 2.34 months. A notable advantage of the rib graft is the absence of a need for an extra incision: the rib bone strut required for grafting is excised during routine anatomical dissection of the surgical procedure.…”
Section: Discussionmentioning
confidence: 83%
“…When anterior spinal surgery and transpleural approaches were commonly used to approach anterior pathologies such as spinal tumors and spinal tuberculosis and perform anterior column fixation, the lateral decubitus position in spine surgery was popular [ 66 , 67 ]. With the development of dependable posterior fixation techniques and access to the anterior column via posterior approaches, the use of anterior approaches in spine surgery has decreased.…”
Section: Other Positionsmentioning
confidence: 99%
“…-Cardiac parameters least affected [42] -Restores lumbar lordosis [57] -Abdomen free and chest and pelvis fully supported [42] -No significant alteration in dynamic pulmonary compliance [59] -Use of image intensifier easy as table radiolucent and free space available -Lower blood loss, low mean airway pressure, and lower intraabdominal pressure compared to Wilson frame [60] -Large and bulky frame [63] -Difficult for the anesthetist to access airway due to large ends of the table [63] -Table height adjustment tedious [63] (Allen's frame) 5 Chest rolls -Cardiac parameters least affected [42] -Significantly decrease dynamic pulmonary compliance [59] -Limited support spine surgery was popular [66,67]. With the development of dependable posterior fixation techniques and access to the anterior column via posterior approaches, the use of anterior approaches in spine surgery has decreased.…”
Section: Lateral Decubitus Positionmentioning
confidence: 99%